Faktor – Faktor Yang Mempengaruhi Kepuasan Pedagang Di Sentra Kue Subuh Pasar Senen Jakarta Pusat - Dimas Prayogo; Anike Suci Badriawan (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aims to analyze the factors influencing trader satisfaction at the Sentra Kue Subuh PasarSenen, Central Jakarta. Using a qualitative descriptive approach, the research involved nine traders,two market managers, and two visitors as informants. Data collection was conducted throughinterviews, observations, and documentation. The findings reveal that factors such as physicalfacilities, management services, security, accessibility, fairness in stall allocation and fees, andeconomic satisfaction significantly affect trader satisfaction. While traders generally expressedsatisfaction, areas needing improvement include cleanliness, air circulation, and parking capacity.This research is expected to serve as input for market management to enhance service quality andtrader comfort, and as a reference for further studies on traditional market management.Keywords: Trader Satisfaction, Market Management, Traditional Market, Service Quality,Qualitative Research